2022
DOI: 10.1007/s00296-022-05171-8
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoidosis with musculoskeletal manifestations: systematic review of non-pharmacological and pharmacological treatments

Abstract: We aimed to summarise effects and use of non-pharmacological and pharmacological treatments for sarcoidosis with musculoskeletal manifestations. We systematically searched the Cochrane Library, Ovid MEDLINE, Embase, CINAHL, AMED, Scopus, clinical.trials.gov, PROSPERO and PEDro for systematic reviews from 2014 to 2022 and for primary studies from date of inception to March 29, 2022, and studies with patients diagnosed with sarcoidosis with musculoskeletal manifestations. Inclusion criteria required that studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…In nonresponsive patients, the use of conventional immunosuppressive drugs is more anecdotal. Methotrexate (7.5 to 15 mg per week) is the most used in musculoskeletal sarcoidosis as a GC-saving agent (39). Other conventional synthetic disease modifying antirheumatic drugs (csDMARDs) such as hydroxychloroquine showed to be effective for the management of vertebral sarcoidosis Studies based on single cases or small series revealed encouraging results.…”
Section: Imaging Featuresmentioning
confidence: 99%
“…In nonresponsive patients, the use of conventional immunosuppressive drugs is more anecdotal. Methotrexate (7.5 to 15 mg per week) is the most used in musculoskeletal sarcoidosis as a GC-saving agent (39). Other conventional synthetic disease modifying antirheumatic drugs (csDMARDs) such as hydroxychloroquine showed to be effective for the management of vertebral sarcoidosis Studies based on single cases or small series revealed encouraging results.…”
Section: Imaging Featuresmentioning
confidence: 99%